The role of carbon labels for consumer decisions: evidence from a class of Chinese students - Liu, Li; Wang, Kaiqing (Frontiers in Climate, 2026)
Although achieving China's “3060” dual-carbon goals is an urgent priority, current research in the field of carbon labeling has paid limited attention to its pathways on consumers' green purchase decision. Drawing on market signaling theory, this paper proposes an innovative purchase decision model for carbon-labeling items. First, based on the theory of action (TRA), we have proposed the hypothesis that subjective norms and attitudes positively influence carbon labeling purchase intentions. Second, we initially extended TRA by incorporating two variables: environmental values and low-carbon knowledge. Finally, we introduce the quality trust variable, offering a completely new viewpoint to extend the TRA model. We adopted a structural equation model (SEM) approach to examine our research model, using 341 samples. The results reveal that consumers' decisions to purchase carbon-labeling items are primarily influenced by their trust in items' quality and attitudes. Additionally, low-carbon knowledge and environmental values directly or indirectly affect purchasing intentions, while subjective norms also demonstrate a positive impact on decision-making. By extending TRA, this study clarifies the decision-making process behind carbon-labeling items consumption, offering significant insights for advancing carbon labeling systems and fostering green consumption trends.